Correction to: Novel characteristics of soluble fibrin: hypercoagulability and acceleration of blood sedimentation rate mediated by its generation of erythrocyte‑linked fibers - Dennis K. Galanakis; Anna Protopopova; Kao Li; Yingjie Yu; Tahmeena Ahmed; Lisa Senzel; Ryan Heslin; Mohamed Gouda; Jaseung Koo; John Weisel; Marilyn Manco‑Johnson; Miriam Rafailovich (Cell and Tissue Research, 2022)

Novel characteristics of soluble fibrin: hypercoagulability and acceleration of blood sedimentation rate mediated by its generation of erythrocyte-linked fibers - Dennis K. Galanakis; Anna Protopopova; Kao Li; Yingjie Yu; Tahmeena Ahmed; Lisa Senzel; Ryan Heslin; Mohamed Gouda; Jaseung Koo; John Weisel; Marilyn Manco-Johnson; Miriam Rafailovich (Cell and Tissue Research, 2022)
Soluble fibrin (SF) in blood consists of monomers lacking both fibrinopeptides A with a minor population in multimeric clusters. It is a substantial component of isolated fibrinogen (fg), which spontaneously self-assembles into protofibrils progressing to fibers at sub-physiologic temperatures, a process enhanced by adsorption to hydrophobic and some metal surfaces. Comparisons of SF-rich (FR) and SF-depleted (FD) fg isolates disclosed distinct molecular imprints of each via an adsorption/desorption procedure using gold surfaced silica microplates. Accelerated plasminogen activator-induced lysis and decreased stiffness (G′) of thrombin-induced FR fg clots were revealed by thomboelastography. Erythrocyte sedimentation (ESR) in afibrinogenemic plasma (Hematocrit 25–33%) was accelerated by FR fg nearly threefold that of FD fg. Stained smears disclosed frequent rouleaux formations and fibers linking stacked erythrocytes in contrast to no rouleaux by FD fg. Rouleaux formations were more pronounced at 4 °C than at ambient temperatures and at fiber-membrane contacts displayed irregular, knobby membrane contours. One of several FR fg isolates also displayed incomplete fiber networks in cell-free areas. What is more, pre-mixing FR fg with each of three monoclonal IgG anti-fg antibodies at 1.5 mol/mol fg, that inhibited fibrin polymerization, prevented rouleaux formation save occasional 2–4 erythrocyte aggregates. We conclude that spontaneously generated SF fibers bound to erythrocytes forming intercellular links culminating in rouleaux formation and ensuing ESR acceleration which in clinical settings reflects hypercoagulability. Also, the results can explain the reported fg binding to erythrocytes via ligands such as CD47, stable in vivo RBC aggregates in capillaries, and red areas of pathologic thrombi.

The characterization and purification of a human transcription factor modulating the glutathione peroxidase gene in response to oxygen tension - Frank Merante; Svetlana M. Altamentova; Donald A.G. Mickle; Richard D. Weisel; Bradley J. Thatcher; Brian M. Martin; John G. Marshall; Laura C. Tumiati; Douglas B. Cowan; Ren-Ke Li (Molecular and Cellular Biochemistry, 2002)